Viridicatin from the Antarctic Fungus Penicillium sp. Protects Human Microglia and Patient-Derived Peripheral Immune Cells Against Oxidative Stress - Cristian Paz; Muhammad Javid Iqbal; Andrea Cristina Paula Lima; Alejandro Luarte; Pablo Lazcano; Ursula Wyneken; María Isabel Behrens; Daniela Ponce; Nicole Jeraldo; Sigisfredo Garnica; Cecilia Villegas; Vaderament-A. Nchiozem-Ngnitedem; et al. (Antioxidants, 2026)
Neurodegenerative diseases remain a major therapeutic challenge, with oxidative stress playing a central role in central and peripheral immune system dysfunction that leads to neuronal loss. Natural products from extreme environments represent an underexplored source of neuroprotective agents. In this study, viridicatin, a quinoline-derived alkaloid, was isolated from the Antarctic fungus Penicillium sp. collected from sediments taken from Deception Island, and its structure was unambiguously confirmed by 1D/2D-NMR spectroscopy and single-crystal X-ray diffraction. Viridicatin (100 µM) significantly attenuated H2O2-induced cytotoxicity in HMC-3 human microglial cells, preserving cell viability and mitochondrial membrane potential. Viridicatin modulated the Nrf2 antioxidant signaling pathway, accompanied by increased expression of the downstream antioxidant enzymes HO-1 and NQO1. Moreover, molecular docking revealed preferential binding to the KEAP1 Kelch domain (−8.0 kcal/mol), suggesting indirect Nrf2 pathway modulation. A 100 ns molecular dynamics simulation with MM-GBSA analysis supported the stability of the viridicatin–KEAP1 complex. Notably, viridicatin rescued peripheral immune cells, i.e., peripheral blood mononuclear cells (PBMCs) obtained from older adults with mild cognitive impairment from H2O2-induced cell death, bridging the gap between in vitro mechanistic evidence and clinically relevant human cellular models. This is the first report of neuroprotective activity for viridicatin, positioning this Antarctic-derived alkaloid as a compelling candidate for further preclinical development against age-related neurodegeneration.